Impact of medication adherence of oral hypoglycemic agents on clinical and economic outcomes: A report from resource-limited settings - Thamineni Rajavardhana; Kadapala Pruthvi Kumar Reddy; Golla Mallikarjuna; Dharmareddy Lakshmanamurthy; Maddirevula Maneesh Kumar Reddy; Easwaran Vigneshwaran (Wolters Kluwer Medknow Publications, 2016)
Background: Achieving medication adherence is a major obstacle for the management of type II diabetes mellitus. Adherence to the prescribed regimen in terms of dose, frequency, and duration is particularly important to combat the existing clinical condition. The present study settings, being a drought area most of the patients are living under miserable conditions and nonadherence may leave the patients with a huge burden of health care cost. Aim and Objectives: To estimate the effect and to correlate the medication adherence on the clinical and economic outcome of patients with anti-diabetic therapy. Methodology: This study is a prospective cohort study carried out in a secondary care referral hospital. Seventy-six subjects were included and conducted with semi-structured interview for the collection of data. Apart from that, other sources such as medical records, labarotory records, and dispensing records were also used for data collection. The study subjects were divided into two groups' viz. good medication adherence and poor medication adherence groups based on their medication possession ratio (MPR). Results: MPR was found to have strong negative correlation to clinical variables such as gross random blood sugar levels. The mean total cost spent by poor medication adherence group subjects was more than ten folds higher than the good medication adherence group. Conclusion: The good medication adherence group was found to be associated with lesser health care cost and better clinical outcome. Hence, it can be considered as one of the possible ways to reduce economic burden and to manage type II diabetes mellitus patients in resource-limited settings.